The little lame prince and The adventures of a brownie - Craik, Dinah Maria Mulock, 1826-1887.; Corcos, Lucille, 1908- (New York, Grosset & Dunlap, 1948)
Five fairy tales: The Little Lame Prince, The Adventures of a Brownie, The Invisible Prince, Prince Cherry, and The Prince with the Nose.
Mode of access: Internet.